Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus, Dan Rasio Pembiayaan Utang Terhadap Transparansi Informasi Keuangan Daerah Via Website - Intan Nurbaiti Fawziah; Fefri Indra Arza (Universitas Negeri Padang, 2020)
The objective of this study determine the effect of Regional Orginal Revenue, General Allocation Funds, Special Allocation Funds, and Debt Financial Ratios to Transparency of Regional Financial Information via Website which is divided to two proxies namely Availability and Accessibility of Regional Financial Information via Website. Sample in this study is the district or city goverment in Indonesia in 2017. Sampling was conducted using a purposive sampling method. The type of data used is secondary data. Independent variable data were obtained from the BPK Audit Reports in 2017 and data obtained from the local goverment website. As for the dependent variable data obtained fro each official site of the local goverment. Data analysis technique used in this study are of two models, namely logistic regression analysis and multiple regression analysis. Result of the test show that Regional Original Revenue has no significant effect on the availability of regional financial via website, Regional Original Revenue has a significant effect on the accessibility of regional financial information via website. General Allocation Funds, Special Allocation Funds and Debt Financial Ratio also do not have a significant effect to availability and accessibility of regional financial information via website.